Elevations of AGE and vascular endothelial growth factor with decreased total antioxidant status in the vitreous fluid of diabetic patients with retinopathy. Issue 6 (27th May 2005) - Yokoi, M; Yamagishi, S-i; Takeuchi, M; Ohgami, K; Okamoto, T; Saito, W; Muramatsu, M; Imaizumi, T; Ohno, S
Abstract : Background/aims: Advanced glycation end product (AGE) induces vascular endothelial growth factor (VEGF) expression in cell culture and animal models, being considered to be involved in development of diabetic retinopathy; oxidative stress also has a part in diabetic retinopathy. However, the interrelations between AGE, VEGF, and oxidative stress remain to be elucidated. In this study, vitreous AGE, VEGF, and total antioxidant levels in were determined in diabetic patients with retinopathy, and the relations among them investigated. Methods: ELISA (enzyme linked immunosorbent assay) was used to determine the vitreous levels of AGE and VEGF in 41 patients with diabetic retinopathy and 28 non-diabetic control subjects. Total antioxidant levels in vitreous of 20 diabetic patients and 18 controls were also analysed by ELISA. Results: The vitreous levels of AGE and VEGF were significantly higher in diabetic patients than in control subjects (p<0.01 for both). There was a significant correlation between the vitreous AGE and VEGF levels (p<0.001). Total antioxidant status was decreased in vitreous in patients with diabetes compared with the controls (p<0.01). Furthermore, both AGE and VEGF levels were inversely correlated with the total antioxidant status (p<0.01 and p<0.05, respectively). Conclusion: This study suggests that AGE and decreased total antioxidant status may contribute to the pathogenesis of diabetic retinopathy via induction of VEGF.